PELIBATAN KOMITE SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN - Dyah Nur Septiana; Ibrahim Bafadal; Desi Eri Kusumaningrum (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2018)
Abstract: This research aims to describe; (1) the strength of the school committee; (2) forms of school committee involvement; (3) the headmaster that strategy involves school committee; (4) obstacles of the school committee; (5) committee’s problem solving alterative in SDN Blimbing 4 Malang. This research uses qualitative approach with case study research type. The data collection techniques are that used observation, interview and documentation. Based on the process of collecting and analyzing, the result of the obtained data are: (1) the strength of the committee derived comes from the readiness, the alertness to solve the problem, the clear division of labor, and the good coordination; (2) forms of committee involvement are: holding meetings, raising funds, controlling the finances, directing and involving parents in the program, reporting the results of activities to parents; (3) the strategy of the headmaster involves the committees are coordinating, approaching, and becoming a role model; (4) the obstacle of school committee constraints such as committee managers are rarely complete during meetings, the guardian objected to donate voluntary; (5) the problem solving alternatives are the absent committee board is replaced by another committee, and take personal approach.Keyword : involvement, school committee, improving the quality of education Abstrak: Tujuan penelitian ini mendeskripsikan; (1) kekuatan komite sekolah; (2) bentuk-bentuk pelibatan komite sekolah; (3) strategi kepala sekolah melibatkan komite sekolah; (4)  kendala-kendala komite sekolah; (5) alternatif pemecahan masalah komite di SDN Blimbing 4 Malang. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Teknik pengumpulan data yang digunakan ialah observasi, wawancara dan dokumentasi. Berdasarkan proses pengumpulan dan analisis data didapatkan hasil, yaitu: (1) kekuatan komite berasal dari keaktifan, kesigapan menindaklanjuti masalah, pembagian kerja yang jelas, dan koordinasi yang baik; (2) bentuk-bentuk pelibatan komite yaitu: mengadakan pertemuan, menggalang dana, mengontrol keuangan, mengarahkan dan melibatkan orang tua dalam program, melaporkan hasil kegiatan kepada orang tua; (3) strategi kepala sekola melibatkan komite yaitu berkoordinasi, melakukan pendekatan-pendekatan, dan kepala sekolah menjadi tauladan; (4) kendala-kendala komite sekolah diantaranya pengurus komite jarang lengkap saat pertemuan, wali murid keberatan saat sumbangan sukarela; (5) alternatif pemecahan masalah yakni pengurus yang tidak hadir digantikan dengan pengurus lainnya, melakukan pendekatan secara personal.Kata kunci: pelibatan, komite sekolah, peningkatan mutu pendidikan